Parametric design of inner teeth of center wheel in electromagnetic harmonic movable teeth transmission. Issue 1 (July 2021) - Yubo, Ren; Yaoyang, MA; Rui, Wan
Abstract: In order to improve the rationality and design efficiency of the structural parameters of the electromagnetic harmonic movable teeth drive system, the rationality of the set parameters is judged based on theoretical calculation, and visual programming is carried out by using VB. The designer only needs to input the set parameters into the specified dialog box to get the corresponding output results, which makes the design of the inner teeth of the center wheel more convenient and fast.